Hubungan antara Iklim Organisasi dan Kepuasan Kerja dengan Motivasi Intrinsik pada Karyawan CV. Sambung Nyowo di Yogyakarta - Rahman, Didik Fauzi (EMPATHY Jurnal Fakultas Psikologi, 2013)
Abstract Â Motivation is an important factor in the success of a company, especially intrinsic motivation. Employees as an engine wheel company must have intrinsic motivation so that the achievement of productivity in a company, but in fact employees of the company CV. Sambung Nyowo not have intrinsic motivation, it is this which encourages researchers to examine the relationship between organizational climate and job satisfaction with intrinsic motivation on employee CV. Sambung Nyowo in Yogyakarta. Subject 40 people and can be analyzed only 31 employees, due to the five employees were not present at the time of deployment scale and four employees did not fill the full scale given that the employee is considered to be the ninth fall. The whole subject is used as a sample or try out unused because the number of subjects is less than 100 then all subjects were taken as samples in order to really be able to present the study population (Arikunto in Drajat, 2010). Data analysis method used in this research is the analysis of the correlation statistic regression. Regression analysis is used because it is a correlational analysis that can be used to examine the relationship between the three variables. The data obtained in this study will be analyzed with the help of the computer to achieve the efficiency of the time, effort and precision of the analysis. The software used was SPSS (Statistical Product and Service sollution) version 16.0 for Windows.Keywords: Organizational Climate, Job Satisfaction, Intrinsic Motivation